Assessment of Postoperative Functional and Aesthetic Outcomes in Patients Undergoing Maxillofacial Reconstruction Following Mandibular Trauma - Uzma Javaid, Hassan Masood, Rashid Javaid, Atif Iqbal Butt, Allah Bux Mushtaq, Saher Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mandibular fractures are the most common maxillofacial injuries and significantly affect mastication, speech, occlusion, and aesthetics. Reconstruction aims not only to restore anatomy but also to re-establish function and appearance, which together determine quality of life. However, regional data on combined functional and aesthetic outcomes following mandibular reconstruction remain scarce. Objectives: To assess postoperative functional and aesthetic outcomes in patients undergoing maxillofacial reconstruction following mandibular trauma. Methods: This prospective observational study was conducted at the Burns and Plastic Surgery Center, Peshawar, and the Department of Surgery, Punjab Dental Hospital, Lahore, from January 2022 to June 2023. A total of 100 patients with traumatic mandibular fractures were included. All underwent open reduction and internal fixation, with autologous bone grafting in selected complex cases. Functional outcomes were assessed by occlusion stability, mastication efficiency, mandibular range of motion, and speech clarity. Aesthetic outcomes were evaluated by surgeon-based assessment of facial symmetry, patient-reported satisfaction using the Visual Analog Scale (VAS), and scar quality with the Vancouver Scar Scale (VSS). Data were analyzed using SPSS v26, with p<0.05 considered significant. Results: Of 100 patients (74 males, 26 females; mean age 31.6 ± 10.2 years), road traffic accidents were the main cause (68%). At six months, 85% achieved stable occlusion, 80% restored mastication, 88% regained normal mandibular mobility, and 86% achieved speech clarity. Surgeon-rated aesthetic satisfaction was 89%, while mean patient VAS score was 8.4. Visible scars and minor asymmetry accounted for dissatisfaction in 22%. Conclusion: Maxillofacial reconstruction after mandibular trauma significantly improves both function and aesthetics. Persistent issues such as speech difficulties and scarring highlight the need for multidisciplinary follow-up to optimize outcomes. Keywords: mandibular trauma, maxillofacial reconstruction, functional outcomes, aesthetic outcomes